Analisis Uji Kesukaan Panelis terhadap Keripik Tempe Berbasis Tepung Singkong dengan Penambahan Tepung Wortel, Tepung Daun Kelor, dan Tepung Kangkung - Annisa Devi Fitriyanti; Niken Purwidiani; Ita Fatkhur Romadhoni; Nufimbar Susy Anindita Handayani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aimed to determine the level of panelists’ preference for tempe chips made from tapioca flour and cassava flour with the addition of carrot flour, moringa leaf flour, and water spinach flour, as well as to identify the most preferred formulation. The research employed an experimental method using a single-factor design, namely the type of fortification flour, consisting of three treatments: K1 (12.5% carrot flour), K2 (12.5% moringa leaf flour), and K3 (12.5% water spinach flour). All treatments used the same basic formulation of 70% tapioca flour and 30% cassava flour. Hedonic testing was conducted with 30 untrained panelists to evaluate color, aroma, taste, texture, and overall acceptability. The data were analyzed using the non-parametric Friedman test at a 5% significance level, followed by the Bonferroni Post-Hoc test when significant differences were detected. The results showed that the type of fortification flour had a significant effect on color (p = 0.003), taste (p < 0.001), and overall acceptability (p < 0.001), but had no significant effect on aroma and texture (p > 0.05). The highest mean score for color preference was obtained by K1 (4.13), followed by K2 (3.63) and K3 (2.97). For overall acceptability, K1 achieved the highest mean score of 4.30, while K2 and K3 obtained scores of 3.40 and 3.17, respectively. The taste attribute of K1 also recorded the highest mean score of 4.33. Furthermore, the Bonferroni Post-Hoc test indicated that K1 differed significantly from K2 and K3. In conclusion, the best formulation was K1, namely tempe chips fortified with 12.5% carrot flour, as it achieved the highest level of panelist acceptance across most sensory attributes. This formulation has the potential to be developed as a functional food product based on local food resources.